Synchronization between Non-autonomous Hyperchaotc Systems with Uncertainties Using Active Control Method - Yadav V.K.; Mishra P.K.; Srivastava M.; Agrawal S.K.; Mishra V. (My University, 2025)
In this article authors have studied the synchronization between non-autonomous hyperchaotic systems viz., Liu and 4D hyperchaotic non-autonomous systems with parametric uncertainties using active control method. The numerical simulation and graphical results shows that the considered method is effective to synchronize non-autonomous hyperchaotic systems with parametric uncertain terms. © 2016 The Authors.